Lazaro Francisco - The Making of a National Artist - Reyes, Soledad S (Archīum Ateneo, 2019)
This essay situates the novels of Lazaro Francisco against the concrete specificities of our history as a nation, from the American colonial regime to the postwar period. The study shows how deeply Francisco understood the concept of nationhood even as he constructed experiences of socio-economic bondage and a disastrous war that resonated with his Liwayway readers.